Evaluation of Student Assessment of the Quality of Matriculation Lecturers of the Theology and Agribusiness Education Study Program, Tribuana Kalabahi University - Selly, Alboin; Molebila, Eunike; Kafelkay, Seprianus; Malese, Lasarus Pelipus (LP. Ma'arif Janggan Magetan, 2024)
The evaluation aims to improve the quality of learning in the matriculation program. By knowing the shortcomings, teachers can improve their learning approaches and methods, so that the final results of the teaching and learning process are more optimal, so that students will get more meaningful learning and in accordance with their academic needs. This study uses a quantitative approach to evaluate the effectiveness of the matriculation program at Tribuana Kalabahi University by collecting numerical data through questionnaires filled out by new students from the Theology and Agribusiness Education Study Program for the 2024/2025 academic year with purposive sampling applied to students who were willing to fill out the questionnaire from a total of 67 students, so that the sample can reflect the proportion of the population. The questionnaire used contains closed questions with a Likert scale of 1-5. The data collected were analyzed using descriptive statistics to provide an overview of the implementation and quality of the matriculation program. The results of the evaluation of the matriculation program at Tribuana Kalabahi University show a generally high level of student satisfaction, with variations in each study program. The Theology Education Study Program received a very good rating with the majority of students feeling very satisfied, while the Agribusiness Study Program was in the fairly good category, although most students felt very satisfied. The percentage of dissatisfaction in Agribusiness indicates the need for evaluation and improvement in several aspects to increase overall satisfaction.